Unilateral choroidal detachment in an elderly patient with Vogt-Koyanagi-Harada disease: a case report and literature review - Peng, Chuzhi; Jiao, Yonghong; Chen, Chunli (Frontiers in Immunology, 2025)
PurposeTo report an uncommon case of Vogt-Koyanagi-Harada (VKH) disease in an elderly patient with unilateral choroidal detachment and describe its multimodal imaging features and prognosis.MethodCase report and literature review of clinical features in VKH with choroidal detachment.ResultsA 76-year-old woman presented with bilateral blurred vision and headache 6 months prior to visiting our hospital. She was diagnosed with iridocyclitis at another hospital and received local anti-inflammatory treatment without improvement. Slit-lamp examination showed bilateral mutton-fat and dust-like keratic precipitates, anterior chamber and vitreous cells, and posterior synechiae in the right eye. Fundus examination revealed bilateral optic disc swelling and choroidal detachment in the left eye. Fluorescein angiography revealed bilateral optic disc leakage, punctate hyperfluorescence in the posterior pole, and elevated fluorescence leakage in the left eye’s temporal area. Indocyanine Green Angiography showed multiple of choroidal hypoperfusion areas in the left eye, with an elevated fluorescence blockage on the temporal side. Optical coherence tomography showed subretinal fluid, wavy retinal pigment epithelium, and choroidal thickening in both eyes. Based on ocular and neurological findings, the patient was diagnosed with bilateral VKH. After ruling out infectious factors, she received high-dose systemic corticosteroids and immunosuppressants. The choroidal detachment and serous retinal detachment gradually resolved.ConclusionThis case is the first report of unilateral choroidal detachment associated with VKH in an elderly patient. VKH patients with choroidal detachment reported in previous studies were predominantly elderly and Asian, characterized by optic disc hyperfluorescence and choroidal detachment. Multimodal imaging can help clinicians better diagnose and manage atypical types of VKH.